INVESTIGATION OF COMPRESSIVE STRENGTH USING ULTRASONIC PULSE VEOCITY METHOD - Deepa Rahane,; Dr.R.M Sawant, (International Journal of Innovations in Engineering Research and Technology, 2021)
There are many methods to access concrete in situ such as non-destructive tests (NDT).  These methods consider indirect measure for assessing the strength of concrete to predict in situ strength. In the present study ultrasonic pulse velocity and rebound hammer test were used for assessing compressive strength of concrete at 7, 28 and 56 days.The rebound hammer test is based on principle that the rebound of an elastic mass depends upon hardness of surface, while the ultrasonic pulse velocity method monitors the internal characteristic of concrete in terms of m/s. These two tests affected by many parameters depends on the nature of production materials in production of concrete, so there is difficulty in determining strength of hardened concrete in situ precisely.Concrete mixes with w/c ratio of 0.30, 0.35, 0.40, 0.45 and 0.50 were cast in the laboratory. The cubes of 150 mm size were tested for compressive strength using UPV, Rebound Hammer and also by crushing at the age of 7, 28 and 56 days of curing. Regression analysis is carried out to establish relation between compressive strength of concrete and results of UPV and Rebound Hammer test. The relations are validated by verifying the results of compressive strength of concrete with w/c ratio of 0.55.